Software essentials : design and construction - Dingle, Adair (Chapman & Hall/CRC Innovations in Software Engineering and Software Development Series., 2014)
About the Cover: Although capacity may be a problem for a doghouse, other requirements are usually minimal. Unlike skyscrapers, doghouses are simple units. They do not require plumbing, electricity, fire alarms, elevators, or ventilation systems, and they do not need to be built to code or pass inspections. The range of complexity in software design is similar. Given available software tools and libraries-many of which are free-hobbyists can build small or short-lived computer apps. Yet, design for software longevity, security, and efficiency can be intricate-